Perfil clínico y epidemiológico de los pacientes con diagnóstico de neurocisticercosis en dos hospitales de Chiclayo, Perú - Rojas-Panta, Giuseppe (2017)
Objective: To describe the clinical and epidemiological profile of patients diagnosed with neurocysticercosis at two hospitals in Chiclayo, Peru. Materials and methods: A descriptive, cross-sectional and retrospective study was performed at the Almanzor Aguinaga Asenjo Hospital and Lambayeque Regional Hospital. Ninety-six (96) medical records of patients attended in 2014 with a diagnosis of neurocysticercosis were reviewed. Results: The mean age of the patients was 42.8 ± 18.8 years old, 52.1% were female, 26% came from Chiclayo and 54.2% received care for the first time. The most common symptom leading to medical consultation was headache. All patients underwent a diagnostic imaging method. The location of the parasite was mostly in the brain and the calcified stage was the most common one. The most widely used treatments were anticonvulsants and pain relievers. Conclusions: Neurocysticercosis mainly affects the economically active population, is more common in women and the most common clinical manifestation is headache.